2013
DOI: 10.1515/hf-2012-0179
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sulfuric acid-assisted glycerol pretreatment of sugarcane bagasse

Abstract: A combined pretreatment of sugarcane bagasse with glycerol and sulfuric acid was investigated based on a central composite rotatable experimental design. The following factors were varied: temperature (150 -199 ° C), time (0.69 -2.3 h), H 2 SO 4 concentration (0.0 -1.1 % ), and glycerol concentration (55.4 -79.6 % ). Xylans and lignin were considerably solubilized during pretreatment. Xylan solubilization, ranging between 6 % and 94 % , increased significantly with the increase of temperature, time, and H 2 SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The delignification results of the AG pretreatments in the present study were consistent with our previous results, 11 but lower than those from several other studies on AG pretreatment. 10,13 The different observations are largely attributable to the different pretreatment conditions, especially pretreatment temperatures. For example, in a recent study, AG pretreatment of sugarcane bagasse at 200 °C for 15 min with 0.6% H 2 SO 4 (on fibre) led to 52% delignification and a glucose yield of 68%.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The delignification results of the AG pretreatments in the present study were consistent with our previous results, 11 but lower than those from several other studies on AG pretreatment. 10,13 The different observations are largely attributable to the different pretreatment conditions, especially pretreatment temperatures. For example, in a recent study, AG pretreatment of sugarcane bagasse at 200 °C for 15 min with 0.6% H 2 SO 4 (on fibre) led to 52% delignification and a glucose yield of 68%.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Glycerol has been used as a standalone solvent, or in combination with alkaline catalysts such as Na 2 CO 3 and NaOH, for delignification (Demirbas ß, 1998;Fu and Mazza, 2011a,b;Novo et al, 2011) and pretreatment of lignocellulosic biomass Chen, 2007, 2008; Wang et al, 2015). Furthermore, recent studies showed that acidified glycerol solutions were very effective in deconstructing lignocellulosic biomass to generate materials with high glucan enzymatic digestibilities (Liu et al, 2010b;Martin et al, 2011Martin et al, , 2013. The authors have previously developed an acid-catalysed and glycerol-based pretreatment process and scaled up this process for pretreatment of sugarcane bagasse from laboratory-scale to pilot-scale (Zhang et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25] Researchers have found that pretreatment with acid-catalysed glycerol or EG solution was more effective than that with polyol alone or alkali-catalysed polyol solution for the pretreatment of lignocellulose. [26][27][28] The disadvantage of these pretreatment systems is that they require relatively high pretreatment temperatures (158-225 °C) in order to achieve cellulose enzymatic digestibility of >90%. [26][27][28][29][30] The initial work by Yamada and Ono established that lignocellulosic biomass can be liquefied in alkylene carbonates, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] The disadvantage of these pretreatment systems is that they require relatively high pretreatment temperatures (158-225 °C) in order to achieve cellulose enzymatic digestibility of >90%. [26][27][28][29][30] The initial work by Yamada and Ono established that lignocellulosic biomass can be liquefied in alkylene carbonates, e.g. ethylene carbonate (EC) and propylene carbonate (PC) in the presence of an acid catalyst.…”
Section: Introductionmentioning
confidence: 99%